SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Nugraha Suminta, Awaliyani; Nindiasari, Hepsi; Mutaqin, Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical creative thinking is an essential skill that supports students in generating diverse ideas and solutions in mathematics learning. However, this skill remains relatively low among students. This study aims to analyze the effectiveness of Problem-Based Learning (PBL) in improving students’ mathematical creative thinking skills through a Systematic Literature Review (SLR). The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including the stages of identification, screening, eligibility assessment, and inclusion. Relevant studies were selected based on predefined inclusion and exclusion criteria focusing on the implementation of PBL in mathematics education and its impact on mathematical creative thinking. The findings indicate that PBL effectively enhances students’ mathematical creative thinking skills by encouraging active engagement in problem-solving, idea exploration, and the development of multiple solution strategies. Furthermore, PBL promotes key indicators of creative thinking, including fluency, flexibility, originality, and elaboration. Therefore, PBL can be considered an effective learning model for fostering students’ mathematical creative thinking skills.